Revised list of diseases reportable to the National Notifiable Diseases Surveillance System - No authors listed (Communicable Diseases Intelligence, 2000)
On 8 February 2000 the Strategic Steering Committee of the Communicable Diseases Network Australia New Zealand agreed to a revised national list of diseases to be reported to the NNDSS.